Processing and Analysis of Electrogastrogram (EGG) Signals to Evaluate Stressor and Motion Sickness Conditions in Virtual Reality Environments - MHD.Hanafi Hanafi; Alvin Sahroni; Sri Kusumadewi; Hendra Setiawan; Firdaus Firdaus (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2026)
Virtual Reality (VR) technology has rapidly evolved and is widely utilized in healthcare, education, and entertainment. However, its use often induces motion sickness and stressor, which may reduce user comfort and performance. This study aims to determine whether VR exposure triggers such conditions, evaluate them using electrogastrogram (EGG) signals, and identify the most effective EGG features as physiological indicators. EGG signals from nine healthy male subjects were recorded using two channels under three experimental conditions (pre, stimulation, and post) during both pre-prandial and post-prandial phases. Frequency-domain analysis was performed using the Fast Fourier Transform (FFT) within the 0.03-0.07 Hz range to extract dominant frequency, dominant magnitude, mean frequency, average magnitude, and band power. Subjective evaluation was conducted using a five-point Likert scale. The results indicate that VR exposure induced motion sickness and stressor, with Likert scores ranging from 3 to 5. Three normalized magnitude features of the EGG signal on channel 0 during the pre-prandial stimulation phase exhibited significant positive correlations with motion sickness: dominant magnitude (r = 0.841, p = 0.005), average magnitude (r = 0.742, p = 0.022), and band power (r = 0.788, p = 0.012). These features also showed significant correlations with stressor levels: dominant magnitude (r = 0.895, p = 0.001), average magnitude (r = 0.780, p = 0.013), and band power (r = 0.821, p = 0.007). These findings confirm that VR exposure can induce motion sickness and act as a physiological stressor, with three EGG magnitude features serving as reliable physiological indicators. The lower corpus extending to the antrum and pylorus was identified as the most representative electrode placement area, and the pre-prandial phase was found to be more susceptible to VR-induced disturbances than the post-prandial phase